2014
DOI: 10.1104/pp.114.251017
|View full text |Cite
|
Sign up to set email alerts
|

Malate Synthesis and Secretion Mediated by a Manganese-Enhanced Malate Dehydrogenase Confers Superior Manganese Tolerance in Stylosanthes guianensis  

Abstract: Manganese (Mn) toxicity is a major constraint limiting plant growth on acidic soils. Superior Mn tolerance in Stylosanthes spp. has been well documented, but its molecular mechanisms remain largely unknown. In this study, superior Mn tolerance in Stylosanthes guianensis was confirmed, as reflected by a high Mn toxicity threshold. Furthermore, genetic variation of Mn tolerance was evaluated using two S. guianensis genotypes, which revealed that the Fine-stem genotype had higher Mn tolerance than the TPRC2001-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 51 publications
(62 reference statements)
1
91
1
Order By: Relevance
“…Under the same conditions, roots of atalmt1 mutants continue to grow normally, because the absence of malate efflux prevents Fe 3+ from accumulating in the apoplast. Some findings in this study appear to contradict Chen et al (2015), who reported that the addition of external malate increased Mn tolerance in yeast (Saccharomyces cerevisiae) and Stylosanthes guianensis, a forage legume species. That study concluded that part of the genotypic variation for Mn tolerance in S. guianensis was attributable to greater malate efflux from roots.…”
Section: Attempts To Mimic the Ox Phenotype In Wild-type Plants With contrasting
confidence: 55%
See 2 more Smart Citations
“…Under the same conditions, roots of atalmt1 mutants continue to grow normally, because the absence of malate efflux prevents Fe 3+ from accumulating in the apoplast. Some findings in this study appear to contradict Chen et al (2015), who reported that the addition of external malate increased Mn tolerance in yeast (Saccharomyces cerevisiae) and Stylosanthes guianensis, a forage legume species. That study concluded that part of the genotypic variation for Mn tolerance in S. guianensis was attributable to greater malate efflux from roots.…”
Section: Attempts To Mimic the Ox Phenotype In Wild-type Plants With contrasting
confidence: 55%
“…Interestingly, the authors mentioned that the ameliorative effects of malate became smaller or even disappeared when malate concentrations were raised (Chen et al, 2015). Therefore, it is possible that even higher concentrations of malate would have increased the toxicity of Mn, as we described here.…”
Section: Attempts To Mimic the Ox Phenotype In Wild-type Plants With mentioning
confidence: 65%
See 1 more Smart Citation
“…Excess Mn can induce brown spots on mature leaves5, interveinal chlorosis, and necrotic and deformed young leaves6. Some plants that adapt well to acid soils may have specific strategies that give them a superior ability to tolerate Mn toxicity3541. After 14 d of treatment, leaf chlorosis was observed in ‘YS’ when cultured in 250 μM MnSO 4 , but not in ‘LJCY’ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Mn is necessary for plant growth and development (Chen et al, 2015). However, excess Mn is toxic to plants.…”
Section: Introductionmentioning
confidence: 99%